1m dance studio student’s use and life influence of weibo - Wei Lili (2022)
With the rapid development of Internet technology and mobile smart devices, social media platforms have become an important medium for the public to obtain information, disseminate information and share opinions, which soon brings human beings into the era of rapid development of social media.With the maturity of physiology, students' self-awareness is also constantly developing, paying more attention to their inner world, of course, but also eager for the attention of the external environment, need to meet psychological emotional demands through communication and interaction with people.In 2010, China began to enter the era of Weibo. As an emerging communication medium, Weibo promoted students' interpersonal communication.Various content editing and interactive sharing functions provided by Weibo greatly deepen the breadth and depth of information dissemination, and also provide a more convenient way for students to participate in. In this thesis, the integrated use of questionnaire, depth interview, text analysis, coupled with some relevant theories of communication and journalism, to 1M Dance Studio students use of Weibo and influence to do in-depth research, and analysis of the causes and effects of Weibo to attract students, the impact problems and how to put forward some Suggestions and countermeasures to solve these problems. The first chapter mainly introduces the source of topic selection, research objectives and scope, as well as the purpose and significance of this research. The second chapter is the literature discussion, which aims to study the use of Weibo by students of 1M Dance Studio, mainly focusing on three themes for literature review. The third chapter is content analysis, which mainly focuses on the research objectives and starts from three survey questions to obtain relevant data and further obtain the final results of the research.